THE EFFECT OF THE ROLE PLAYING LEARNING MODEL ON STUDENTS' SELF-CONFIDENCE IN THE INDONESIAN LANGUAGE SUBJECT AT SDN SEMPU 1 - Hilda Dhaniartika Nurma'ardi; Sobilatus Syifa; Ika Evitasari Aris; Maya Kuswaty (STMIK Indonesia Banda Aceh, 2026)
This study aims to determine the effect of the Role Playing Learning Model on Students' Self-Confidence in the Indonesian Language Subject of Grade V of Sempu 1 State Elementary School. The focus of the study was directed to determine whether the role playing model has an effect on students' self-confidence in learning Indonesian. The research method used was a quantitative method of the pre-experimental type with a one-group pretest-posttest design. The study was conducted at Sempu 1 State Elementary School with the population being all students at the elementary school and the sample being all fifth-grade students totaling 29 people who were determined through purposive sampling techniques for certain reasons. The research instruments included a self-confidence questionnaire, observation sheets, and interview guidelines. Data were collected through questionnaires, pretests, posttests, observations, and interviews. The data analysis technique used was the Paired Sample T-Test to determine the difference in the results of the pretest-posttest of students' self-confidence. The results showed that the role playing model had a positive effect on learning Indonesian, evidenced by the significance value of the T-test of 0.000 <0.05. The results of observations, questionnaires, and interviews supported that students became more confident, brave to appear, optimistic, and responsible in learning. It was concluded that the role playing model is suitable for implementation to support Indonesian language learning in elementary schools, with suggestions for teachers to combine this model with other strategies to optimize the increase in students' self-confidence.